Islam dan Lembaga Negara dalam Al-Qur’an - Alya Agustina; Asri Muthiyal Haq; Dida Maulidah Rukoyah; Dini Fitriyani; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to explain the concept of state institutions using the maudhu'i interpretation approach. This research uses a qualitative method of literature study. State institutions are bodies (organizations) whose purpose is to carry out a scientific investigation or carry out a business. In the Qur'an there are several state terms, namely balad, bilad, baldatun, qoryah, and ad-dar. State institutions can help achieve state goals if their principles and criteria are in accordance with good and correct regulations.